Development and pilot testing of the revised Patients' Attitudes Towards Deprescribing questionnaire for people with cognitive impairment. (6th August 2018) - Reeve, Emily; Anthony, Allicia C; Kouladjian O'Donnell, Lisa; Low, Lee‐Fay; Ogle, Susan J; Glendenning, James E; Lorang, Catriona EB; Hilmer, Sarah N
Abstract : Objectives: (i) To develop a version of the revised Patients' Attitude Towards Deprescribing (rPATD) questionnaire for people with mild cognitive impairment (MCI) and mild‐to‐moderate dementia (rPATDcog); and (ii) to capture the beliefs and attitudes of this population and their carers about deprescribing through a pilot study. Methods: First, the rPATDcog was modified from the rPATD and tested in a small group of participants with MCI or mild dementia, and then, we conducted a pilot study of the rPATDcog and the carers' rPATD. Results: Twenty‐one participants with cognitive impairment and 11 carer participants (forming dyads) participated in this study. Eighty‐one per cent (17/21) of participants said that they would stop one or more of their medications if their doctor said it was possible. There was an excellent agreement of corresponding questions between dyads. Conclusion: The rPATDcog was feasible to administer in this study. Further work is required to provide generalisable results and determine utility in practice.